From Competency Mapping to Digital Twin Integration: Developing a Next-Gen Digital Project Manager Model for Smart Construction - Owais, Omar A; Poshdar, Mani; GhaffarianHoseini, Ali; Ying, Fei; Jaafar, Kamal; Sarhan, Saad; Sheikhkhoshkar, Moslem (International Council for Research and Innovation in Building and Construction, 2025)
The digital transformation of the construction industry has outpaced the evolution of traditional project management competency frameworks, leaving many Project Managers (PMs) underprepared to meet the demands of emerging technologies such as Digital Twins (DTs). This study develops and validates a Next-Gen Digital PM Competency List tailored to the Smart Built Environment (SBE) through a structured two-stage methodology. Stage 1 applied a three-phase process comprising (1) a Systematic Literature Review (SLR), (2) NVivo-based thematic analysis, and (3) Large Language Model (LLM)-driven synthesis. These phases identified, categorised, and defined 55 digital PM competencies, systematically organised into Skills, Knowledge, and Core Personality Traits. Stage 2 evaluates the practical relevance of these competencies by mapping them against six thematic functional requirements of DTs, including interoperability and integration, real-time data management, simulation and predictive modelling, cybersecurity and data governance, stakeholder collaboration, and scalability and lifecycle continuity. DTs were selected as an exemplar because they integrate multiple digital technologies, Building Information Modelling (BIM), Internet of Things (IoT), Artificial Intelligence (AI), and cloud computing, making them a representative test case for evaluating competency alignment in digital transformation. The mapping confirmed strong alignment in digital integration and collaboration while exposing gaps in cybersecurity readiness and lifecycle resilience. The resulting framework provides a validated reference for competency benchmarking, targeted training, and digital leadership development. By equipping PMs with the competencies to lead, manage, and support digitally enabled projects, this research contributes directly to advancing smart and sustainable construction practices in the digital built environment.
Keywords: 4005 Civil Engineering; 40 Engineering; 33 Built Environment and Design; 3302 Building; Networking and Information Technology R&D (NITRD); Machine Learning and Artificial Intelligence; 9 Industry, Innovation and Infrastructure; 0899 Other Information and Computing Sciences; 0905 Civil Engineering; 1202 Building; Building & Construction; 3302 Building; 4005 Civil engineering